Effect of self-ion irradiation on hardening and microstructure of tungsten. (December 2016) - Hwang, T.; Fukuda, M.; Nogami, S.; Hasegawa, A.; Usami, H.; Yabuuchi, K.; Ozawa, K.; Tanigawa, H.
Highlights: 18MeV W 6+ irradiation to pure W and W–3% Re was conducted at 500 and 800°C. Voids were observed in all of specimen without W–3% Re irradiated to 0.2 dpa. Irradiation hardening was saturated in pure W after 1 dpa irradiation. After 5 dpa irradiation, irradiation hardening of W–3% Re was smaller than pure W. Abstract: The irradiation hardening and microstructures of pure W and W – 3% Re for up to 5.0 dpa by self-ion irradiation were investigated in this work. The ion irradiation was conducted using 18 MeV W 6+ at 500 and 800 °C. A focused ion beam followed by electro-polishing was used to make thin foil specimens for transmission electron microscope observations. Dislocation loops were observed in all the irradiated samples. Voids were observed in all of the specimens except the W–3% Re irradiated to 0.2 dpa. The hardness was measured by using nanoindentation. The irradiation hardening was saturated at 1.0 dpa for pure W. In the case of W – 3% Re, the irradiation hardening showed a peak at 1.0 dpa. The correlation between the microstructure and hardening was investigated.